PENGARUH MEDIA SOSIAL INSTAGRAM @FYINDONESIANS TERHADAP KEBUTUHAN INFORMASI KANDUNGAN GULA PADA KOPI READY TO DRINK - Amarilia Shinta; Vera Wijayanti Sutjipto; Maulina Larasati Putri (Linimasa : Jurnal Ilmu Komunikasi, 2023)
Currently, circulating health information aims to create awareness in the community about adopting healthy living behaviors. Social media which is included in the new media section is widely used by the public to obtain information. Social media has the advantage of being a digital communication tool capable of spreading health messages and information to the public, such as Instagram which is chosen and used by Indonesian people. Instagram users have the opportunity and freedom to produce, distribute and consume the content. Instagram account @fyindonesians as an active media user utilizes Instagram to share information and educate the public regarding sugar-sweetened beverages (SSBs). Sugar-sweetened beverages (SSBs) are still consumed by Indonesian people. The Indonesian Ministry of Health stated that excessive consumption of that product could increase the risk of cancer, diabetes, hypertension, heart disease, and even death. The intention of this research is to find out the effect of social media Instagram @fyindonesians on the information needs on sugar levels in ready-to-drink coffee. The theory used is the uses and gratifications theory. The research population was 2019 students of Communication, Universitas Negeri Jakarta, with a total of 81 students. The sample used in this study was 63 samples. The results show t count > t table (9,619 > 2,388) which means Ha is accepted. The results also show a significance value of 0.013, by this significance represents that this research has a significant effect.   Currently, circulating health information aims to create awareness in the community about adopting healthy living.